2013
DOI: 10.1155/2013/690329
|View full text |Cite
|
Sign up to set email alerts
|

Does Percutaneous Kyphoplasty Have Better Functional Outcome Than Vertebroplasty in Single Level Osteoporotic Compression Fractures? A Comparative Prospective Study

Abstract: Purpose. To evaluate the relative differences in surgical outcome of kyphoplasty (KP) versus vertebroplasty (VP) in the patients with single level refractory osteoporotic compression fractures (OCFs). Method. From August 2008 to May 2012, we intermittently treated 57 patients with single level OCF by PV and KP (Groups A and B, resp.). We used visual analogue scale (VAS) and short form 36 (SF36) questionnaire to measure functional recovery and followed them for six months. Independent samples t- and Kendall's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…After literature identified and examined, all the data in this network meta-analysis were extracted from 32 trials with 2,852 subjects [Grohs et al, 2005;Pflugmacher et al, 2005;De et al, 2007;Voormolen et al, 2007;Al-Qazaz and Elshafey, 2012;Zhou et al, 2008;Buchbinder et al, 2009;R€ ollinghoff et al, 2009;Schofer et al, 2009;Bae et al, 2010;Kasperk et al, 2010;Klazen et al, 2010;Kumar et al, 2010;Movrin et al, 2010;Rousing et al, 2010;Farrokhi et al, 2011;Folman and Shabat, 2011;Blasco et al, 2012;Kallmes, 2012;Movrin, 2012;Endres and Badura, 2012;Li et al, 2012;Omidikashani et al, 2012;Van Meirhaeghe et al, 2013;Chen et al, 2014;Du et al, 2014;Kroon et al, 2014;Liu et al, 2015;Wang et al, 2015Wang et al, , 2016Clark et al, 2016;Yang et al, 2016], compared the efficacy of PKP, PVP and CT in the aspects of VAS, ODI, KA, and the occurrence of fracture, the primary traits were listed in the Table I, indicating that the average age of the patients are above 60 and large portion of them are female. Among these 32 trials, VAS was the most frequent outcome, reported by all the trials except one.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…After literature identified and examined, all the data in this network meta-analysis were extracted from 32 trials with 2,852 subjects [Grohs et al, 2005;Pflugmacher et al, 2005;De et al, 2007;Voormolen et al, 2007;Al-Qazaz and Elshafey, 2012;Zhou et al, 2008;Buchbinder et al, 2009;R€ ollinghoff et al, 2009;Schofer et al, 2009;Bae et al, 2010;Kasperk et al, 2010;Klazen et al, 2010;Kumar et al, 2010;Movrin et al, 2010;Rousing et al, 2010;Farrokhi et al, 2011;Folman and Shabat, 2011;Blasco et al, 2012;Kallmes, 2012;Movrin, 2012;Endres and Badura, 2012;Li et al, 2012;Omidikashani et al, 2012;Van Meirhaeghe et al, 2013;Chen et al, 2014;Du et al, 2014;Kroon et al, 2014;Liu et al, 2015;Wang et al, 2015Wang et al, , 2016Clark et al, 2016;Yang et al, 2016], compared the efficacy of PKP, PVP and CT in the aspects of VAS, ODI, KA, and the occurrence of fracture, the primary traits were listed in the Table I, indicating that the average age of the patients are above 60 and large portion of them are female. Among these 32 trials, VAS was the most frequent outcome, reported by all the trials except one.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…When comparing VP with KP, it seems that both procedures offer a 4-5 point average reduction from baseline (in a 10-point scale), so most authors believe that the threshold for performing the procedure is a preoperative Visual Analogue Scale (VAS) pain score of at least 4 or 5 [2940]. Few studies report better pain relief from KP up to 1-2 years postoperatively [41, 42].…”
Section: Pain Relief/disability/qol Improvementmentioning
confidence: 99%
“…Cement-based treatment algorithms play the major role in this age group regardless of the fracture severity. Fractures that involve the dorsal wall are at risk for cement-associated problems like leakage into the disc space or even into the epidural space besides physical cement-associated problems like exothermic reactions during the polymerization progress that might injure adjunct neuro-vascular structures [ 11 , 13 , 16 , 17 ]. Internal fixation devices turn to break out or displace in patients with reduced bone quality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%